The Normal Anterolateral Ligament of the Knee according to Ultrasound Examination - Kostrub, O.O.; Кotiuk, V.V.; Luchko, R.V.; Blonskyi, R.I.; Vadziuk, N.S.; Didukh, P.V. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Ultrasonographic parameters of the anterolateral ligament (ALL), a recently described anatomical structure, are essential to have a starting point in its injury diagnostics.Objective: to determine the ultrasonographic parameters of the normal ALL.Materials and Methods. We studied 47 volunteers (94 joints) without a history of injuries of the knee joints with a multi-frequency linear sensor Philips HD-11 XE #USD0874946.Results. The ALL was visualized in all 94 knee joints. The ALL looked like an anisotropic fibrillar structure and seemed to be symmetrical in 93.62% of patients. We were able to assess the integrity of the ALL in only 82.98% of the knee joints. The minimum thickness of the ALL was always in its meniscal part (1.43±0.54 mm). The thickest part was the area of attachment to the tibia (3.26±0.47 mm); the width of the tibial ALL attachment was 12.83±2.64 mm. The thickness of the ALL femoral attachment was difficult to estimate in most cases due to the braiding of the ALL and fibular collateral ligament fibers together. We could visualize the tibial and meniscal portion in 100%, femoral – in 95.74%, and menisco-tibial – in only 4.26%. There is a violation of the cortical layer integrity at the site of the tibial ALL attachment in at least one knee joint in 25.53% of patients without a history of injuries.Conclusions. The contralateral knee joint ALL may be a valid reference for ultrasonographic comparison for the injured ALL. Ultrasonographic signs of the cortical layer discontinuity at the tibial ALL attachment are not indisputable symptoms of Segond fracture.